PENGGUNAAN KELERENG SEBAGAI PENGGANTI KERIKIL PADA CAMPURAN BETON - - Sriliani; Andry ALim Lingga; Gatot Setya Budi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Concrete is the most widely used building material in the world, including Indonesia. By building concrete we have dams, pipelines, drainage, foundations, piling, bridge, highway to skyscrapers. A large number of concrete in construction results the increasing need for concrete material, thus triggering rock mining on a large scale. It decreases the number of natural resources that are available for concreting. It also damages the   environment. Hence, considering the new procurement for aggregate resources in the concrete manufacture is needed, for example by replacing the coarse aggregate / gravel with marbles. This research aims to make concrete by using marbles, with 20 MPa compressive strength target plan, using the Holcim cement brands with 7-10 cm slump. In the manufacture of specimens test, the researchers used the modified ACI method. The marbles used were divided into two variations: marbles with the slippery surface / plain and roughened marbles. The test committed against the concrete is compressive strength test, tensile and modulus of elasticity sides. The test shows that the compressive strength of concrete meets the target plan of 20 MPa. The results are 32.511 MPa compressive strength characteristics for marbles slippery surfaces and 27.371 MPa compressive strength characteristics for rough surface aggregate concrete. The results obtained a significant difference range caused by the same marbles gradation with ≥ 40% abrasion on rough surfaced marbles and different value slump. Keywords: Marbles,  Tensile crack, Modulus of Elasticity.